EVALUATING THE EFFECTIVENESS OF SCHOOL SAFETY ZONES ON A NATIONAL ARTERIAL ROAD: EVIDENCE FROM MANADO CITY, INDONESIA - Gracia Mizuno Elisa Sompie; Johan Reineer Tumiwa; Main Al-Dalahmeh; Adrian Nagy (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
This study embodies the implementation and effectiveness of the School Safety Zone (ZoSS) at Pertiwi Junior High School and Senior High School in Manado, located on Jalan A.A. Maramis, a national arterial corridor in Manado City. The research method used a field survey with facility compliance analysis based on the Decree of the Director General of Land Transportation No. SK.3582/AJ.403/DRJD/2018, traffic performance assessment according to the 2023 Indonesian Road Capacity Guidelines (PKJI), and a Two-Sample T-Test statistical test. The evaluation results showed that several ZoSS facilities did not fully meet technical standards due to faded road signs and damaged signs. Statistical analysis confirmed a significant decrease in vehicle speed after entering the ZoSS area. However, its effectiveness is still limited because the majority of drivers continue to drive above the speed limit of 30 km/h. Meanwhile, road performance remains stable at level of service (LOS) C with a degree of saturation value between 0.456 and 0.681. In conclusion, the current implementation of ZoSS is not optimal in controlling vehicle speed and improving pedestrian safety. Technical infrastructure improvement steps are needed.